The Strengths of Reading Materials in Students’ Worksheet Used at Second Grade of SMA N 9 Kota Jambi - Poniyem Poniyem; Wennyta Wennyta (Universitas Batanghari Jambi, 2021)
The aims of the study were to find out the strengths of reading materials in students’ worksheet: Talk Active 2 used at Second Grade of SMA N 9 Kota Jambi meet the criteria of good learning materials. Those criteria are: (1) The materials make clear the link between the classroom and the wider world (2) The materials foster independent learning (3) The materials focus the learner on the the opening process (4) The materials are readily available. The student worksheet was written by Fx. Sukristiono, Nursahid, Sudarso, and published by Yudhistira. The research is expected to give insights of understanding the quality of reading materials. This study was designed as a documentary analysis in the form of descriptive qualitative research in which the result would be described in the form of words. The data were collected from the reading section in the students’ worksheet. As supplementary tools of the instrument, forms of checklist were used during the research analysis. The researcher concluded that most of students easy to understand about content of the text but, they still have difficulty in understand the reading materials about definitions, generic structures and functions of each text. Because, most of the texts only present the example of each text. The students need the worksheet should be clearer in reading materials. Not only provide a lot of exercise but also the clear explanations about the definitions, generic structure, purpose, language features and usage of tenses.The result of identified reading materials in students’ worksheet shows some strengths, they are; 1) Common vocabulary for second grade of senior high school, 2) Each text types in students’ worksheet has more than one text, 3) There are learning materials in students’ worksheet.Key Words: Strengths, Reading Materials, Students’ Worksheet.